MOCK IMPOLITENESS AND SYMBOLIC INTERACTIONISM IN KI SENO NUGROHO’S JAVANESE SHADOW PUPPET SHOW - Prakoso, Imam (LLT Journal: A Journal on Language and Language Teaching, 2024)
This research aims to investigate the use of mock impoliteness in Ki Seno Nugroho’s shadow puppet performances and the formation of symbolic interactionism between the puppeteer and the audience. This is due to the evolving forms of politeness within Javanese society, particularly in the realm of shadow puppet performances in the modern era. Additionally, there is a public perception of Ki Seno Nugroho as a humorous puppeteer using Bagong as a means of communication during his performances. The analysis of conversations between Bagong and other characters is used to explore the context of mock impoliteness and symbolic interactionism in Ki Seno Nugroho’s shadow puppet shows titled “Bagong Duta,” “Bagong Maneges,” and “Semar Mbangun Kayangan.” The results of this study indicate that the use of mock impoliteness serves to create a humorous atmosphere, thus enhancing the entertainment aspect of Ki Seno Nugroho’s shadow puppet performances. Moreover, it seems that Ki Seno Nugroho successfully portrays Bagong in three forms of symbolic interactionism: as a physical entity (the youngest son of Semar, the father of all panakawan characters in the Javanese puppet shadow story), a social entity (a representation of resistance by the common people towards authority), and an abstract entity (an entertainment element in shadow puppet performances).